Diet‐tissue discrimination factors and turnover of carbon and nitrogen stable isotopes in tissues of an adult predatory coral reef fish, Plectropomus leopardus. (2nd December 2015) - Matley, J. K.; Fisk, A. T.; Tobin, A. J.; Heupel, M. R.; Simpfendorfer, C. A.
Abstract : Rationale: Stable isotope ratios (δ 13 C and δ 15 N values) provide a unique perspective into the ecology of animals because the isotope ratio values of consumers reflect the values in food. Despite the value of stable isotopes in ecological studies, the lack of species‐specific experimentally derived diet‐tissue discrimination factors (DTDFs) and turnover rates limits their application at a broad scale. Furthermore, most aquatic feeding experiments use temperate, fast‐growing fish species and few have considered medium‐ to large‐sized adults with low growth rates from tropical ecosystems. Methods: A controlled‐diet stable isotope feeding trial was conducted over a 196‐day period for the adult predatory reef fish leopard coralgrouper ( Plectropomus leopardus ). This study calculated δ 13 C and δ 15 N DTDFs and turnover rates in five tissues (liver, plasma, red blood cells (RBC), fin, and muscle) using a continuous flow isotope ratio mass spectrometer equipped with an elemental analyzer. In addition, the effect of chemical lipid extraction (LE) on stable isotope values was examined for each tissue. Results: Turnover was mainly influenced by metabolism (as opposed to growth) with LE δ 15 N half‐life values lowest in fin (37 days) and plasma (66 days), and highest in RBC (88 days) and muscle (126 days). The diet‐tissue discrimination factors for δ 15 N values in all tissues (Δ 15 N: –0.15 to 1.84‰) were typically lower than commonly reported literature values. Lipid extraction altered both δ 15 N and δ 13 C values compared with untreated samples; however, for the δ 15 N values, the differences were small (mean δ 15 NLE‐Bulk <0.46‰ in all tissues). Conclusions: This study informs future interpretation of stable isotope data for medium‐ to large‐sized fish and demonstrates that DTDFs developed for temperate fish species, particularly for δ 15 N values, may not apply to tropical species. Sampling of muscle and/or RBC is recommended for a relatively long‐term representation of feeding habits, while plasma and/or fin should be used for a more recent indication of diet. Copyright © 2015 John Wiley & Sons, Ltd.